2018
DOI: 10.1103/physrevb.98.054431
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure investigations on the semi-Heusler compound CuMnSb

Abstract: The antiferromagnetic semi-Heusler compound CuMnSb has been investigated under high pressure by electrical resistivity and angle dispersive synchrotron x-ray diffraction measurements to 53 and 36 GPa, respectively. The Néel temperature at ∼50 K is found to initially increase rapidly with pressure, reaching 83 K at 7 GPa. However, near 8 GPa at ambient temperature a sluggish first-order structural transition begins from a semi-metallic cubic phase to a likely semi-metallic tetragonal phase; thermal cycling to 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 45 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The experimental confirmation of topological nature of materials studied can be done through several experiments like angle resolved photo-emission spectroscopy measurements [50], magneto-transport [51] and quantum oscillations in resistance of material as a function of magnetic field (the Shubnikov-de Hass effect) and NMR study [52][53][54][55]. Also, there are several experimental reports which are relevant to pressure dependent synthesis of the half-Heusler materials via various techniques like diamond anvil cell [56][57][58]. We expect that the findings reported here will further encourage the quest for topological insulating behaviour in half-Heusler compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The experimental confirmation of topological nature of materials studied can be done through several experiments like angle resolved photo-emission spectroscopy measurements [50], magneto-transport [51] and quantum oscillations in resistance of material as a function of magnetic field (the Shubnikov-de Hass effect) and NMR study [52][53][54][55]. Also, there are several experimental reports which are relevant to pressure dependent synthesis of the half-Heusler materials via various techniques like diamond anvil cell [56][57][58]. We expect that the findings reported here will further encourage the quest for topological insulating behaviour in half-Heusler compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The electronic properties of NiXSn(X = Zr, Hf) alloys [28] have been investigated using ab initio calculations and conversion from the indirect to direct band gap at 50 GPa and 127 GPa for NiZrSn and NiHfSn alloys, respectively. CuMnSb semi-Heusler alloys [29] were measured under pressure, and it was found that the Neel temperature of CuMnSb increased with pressure. The semimetallic cubic phase becomes the semimetallic tetragonal phase at about 8 GPa.…”
mentioning
confidence: 99%